(3CSGSjGJ aj GdVQjHI GdeMdjI hGdOhdjI s - (3ehdhO(B, (3edjcGhjs ((3GdLRGFQ(B:s (3OGQ gheI(B,s, 2018)
(3GdEWGQ GdfXQj ddVQjHI hGdSjGSI GdVQjHjI hGdJgQH GdVQjHj GdOGNdj ,GdYah GdVQjHj eY GdEROhGL GdVQjHj GdeMdj hGdVQGFH aj YGde GdCYeGd GdEdcJQhfjI, jhLO CjVG eaghe hWQb JbOjQ JcGdja GdEfaGb GdVQjHj, GdELGRI GdVQjHjI hGdaQGZ GdVQjHj hCjVG GdEROhGL hGdJgQH hGdJfSjb GdVQjHj GdOhdj hGdedGPGJ GdVQjHjI(B.s
(3eQGLY U(B.245s
Keywords: (3GdGROhGL GdVQjHjs; (3GdVQGFH GdeMdjIs; (3GdVQGFH(B- (3JgQHs